Ultra-high fire-safety unsaturated polyesters enabled by self-assembled micro/nano rod from Schiff base, diphenylphosphinyl group and nickel (II) metal. (1st August 2022) - Li, Zhen; Fu, Teng; Lu, Jia-Hui; He, Jie-Hao; Li, Wen-Da; Liu, Bo-Wen; Chen, Li; Wang, Yu-Zhong
Abstract: As one of the most flammable common commercially resins, high flammability and heat/smoke release characteristics of unsaturated polyesters (UP) lead to severe casualties and irreparable property loss. To solve these problem, a flame-retardant approach via the multiple synergic effects of promoting char-ability, physically shielding heat/mass transfer, and quenching small molecular fragments in burning is proposed. Herein, a novel micro/nano rod flame retardant SDPPNi, composed of diphenylphosphinyl groups, Schiff base and Nickel (II), are synthesized by self-assembly based on the coordination reactions. The UP with 25 wt% SDPPNi (UP/SDPPNi25), shows quite excellent fire-safety performance, and its limiting oxygen index (LOI) is as high as 38.0%, showing extremely high flame retardant efficiency. Meanwhile, its peak heat release rate (PHRR), total heat release (THR), fire growth rate (FIGRA), and maximum smoke density (Dsmax ) values are significantly reduced by 69%, 40%, 72%, and 42%, respectively. During burning, the SDPPNi promotes UP to form compact char layers composed of pyridine derivatives, phosphoric-oxygenic compounds, and nickel-oxides, inhibiting the heat and mass transfer. Meanwhile, the SDPPNi also releases phosphorous-containing volatiles that can capture some small molecular fragments and break off the chain reaction of combustion. Therefore, a state-of-art strategy is proposed to endow UP resins with ultra-high fire-safety performance. Graphical abstract: Image 1 Highlights: A multiple-synergistic flame-retardant strategy for unsaturated polyesters resins. Novel micro/nano rods are synthesized via self-assembly of coordination. Simultaneous realization of ultra-high fire safety and ultra-low heat/smoke release.